2019
DOI: 10.1002/jso.25689
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic index of lymphadenectomy among patients with pancreatic neuroendocrine tumors: A multi‐institutional analysis

Abstract: Background: The benefit derived from lymph node dissection (LND) in patients with pancreatic neuroendocrine tumors (pNETs) based on clinicopathological characteristics remains unclear.Methods: Patients undergoing surgery for pNET between 1997 and 2016 were identified using a multi-institutional dataset. The therapeutic index of LND relative to patient characteristics was calculated.Results: Among 647 patients, the median number of lymph nodes (LNs) evaluated was 10 (interquartile range: 4-16) and approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…While LND is performed to adequately stage the disease and limit the locoregional tumor spread, the therapeutic index focuses more on the latter and aids in the identification of patients who will benefit the most from LND. Although the therapeutic index was first proposed in the treatment of gastric cancer, investigators have recently applied this concept to different types of malignancies, including colorectal and pancreatic cancer as well as intrahepatic cholangiocarcinoma . Nevertheless, to date, the nodal therapeutic index has not been examined among patients undergoing resection for GBC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While LND is performed to adequately stage the disease and limit the locoregional tumor spread, the therapeutic index focuses more on the latter and aids in the identification of patients who will benefit the most from LND. Although the therapeutic index was first proposed in the treatment of gastric cancer, investigators have recently applied this concept to different types of malignancies, including colorectal and pancreatic cancer as well as intrahepatic cholangiocarcinoma . Nevertheless, to date, the nodal therapeutic index has not been examined among patients undergoing resection for GBC.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic index is based on the rationale that lymphadenectomy may be most important among patients with a high estimated frequency of LNM, as well as individuals who are most likely to gain a survival benefit from the ascertainment of nodal status information . Nodal therapeutic index was first applied to determine the survival benefit of lymphadenectomy for gastric cancer, and more recently has been applied to patients with colorectal and pancreatic malignancies . Furthermore, the therapeutic index has been employed to define optimal LND in the Japanese Classification of Gastric Carcinoma guidelines, indicating the increasing adoption of this concept .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the comparable long-term outcomes were attained despite differences in TNLE among patients undergoing SPDP versus DPS. While LN involvement has been demonstrated to be prognostic in some studies [26,29,30], other data have suggested that TNLE and LNM may not be as prognostically important among patients with pNET that have other favorable features such as ≤2 cm, Ki-67 < 3% [31]. To this point, Mao et al [32] reported that lymphadenectomy had no additional therapeutic benefit among patients undergoing resection for pNETs of the pancreatic body or tail.…”
Section: Discussionmentioning
confidence: 99%
“…EN does not, however, involve resection of the tumor with a wide resection margin and lymphadenectomy is generally not performed at the time of EN, which could potentially compromise oncological outcomes. 12,13 To date, no clear recommendations exist around the indications regarding EN for pNETs. In addition, the majority of available studies report data from single center experiences or describe patients with a pNET as part of a larger study population, and, thus, the safety and efficacy of EN have not been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%